Regenerasi Vegetasi Tingkat Pohon di Kawasan Penyangga Cagar Alam Cycloops, Kelurahan Entrop Distrik Jayapura Selatan, Kota Jayapura - Suharno Suharno; Alfred A. Antoh (Jurusan Biologi FMIPA Universitas Cenderawasih, 2009)
A study on the regeneration of vegetation at trees level was conducted in buffer zone of Mt. Cycloops Nature Reserve in Entrop, Jayapura Selatan. The field research was done for three months from May to July 2008 using the kuadrad method developed by Muller-Dumbois and Ellenberg (1974). Identification of the trees species was conducted in the laboratorium of Biology Department, Cenderawasih University. Several species were sent to Herbarium Manokwariense for further identification. The results reveal that there were 43 species of trees in the given area. These vegetation type were dominated by Sapindaceae, Caecalpiniaceae, Lauraceae, Burseraceae, and Euphorbiaceae. It was found that the regeneration of trees vegetation was not optimal, because the number of trees having trunk diameter 10–25 cm was relatively lower than those with diameter 25–50 cm. Human activities in utilizing the forest area have affected the regeneration process.Key words: vegetation structure, regeneratiion of vegetation, Cycloops, Jayapura.